STRATEGI PEMBELAJARAN LISTENING TEAM UNTUK MENGATASI KESULITAN KONSENTRASI BELAJAR (STUDI KASUS SMK AL-FATTAH PUNGPUNGAN KALITIDU BOJONEGORO) - Abdul Jalil; Aya Mamlu’ah; Afshahun Natiq (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
The learning process must be carried out by a teacher, learning according to what is desired or expected. These learning processes determine the extent to which students understand and accept the material presented. However, in reality, there are still many problems in the learning process in the classroom that have not run optimally. One of them is students who have difficulty concentrating in PAI subjects, this is because a teacher still uses the classic method, namely the lecture method and the class environment is less conducive. To overcome these problems PAI teachers must apply active learning strategies, one of which is the Listening Team learning strategy. The Listening Team expansion strategy is a learning strategy by creating teams or groups according to their respective roles and tasks. The formulation of the research problem is how to apply the Listening Team learning strategy to overcome difficulties in learning concentration at al-Fattah Pungpungan Kalitidu Bojonegoro Vocational School? The research method that the author uses is a qualitative research method. Data collection techniques are observation, interviews, documentation. Data analysis techniques use data reduction, data display, and conclusion drawing/verifying. To check the validity of research data using triangulation techniques. The results of this study show that the implementation of the Listening Team learning strategy to overcome difficulties in learning concentration at al-Fattah Pungpungan Kalitidu Bojonegoro Vocational School has been implemented properly, namely, with lesson planning, the application of the Listening Team strategy, and evaluation of appropriate learning outcomes.